Ab Initio Wavefunction Analysis of Electron Removal Quasi-Particle State of NdNiO2 With Fully Correlated Quantum Chemical Methods - Katukuri, Vamshi M.; Bogdanov, Nikolay A.; Alavi, Ali (Frontiers in Physics, 2022)
The discovery of superconductivity in hole-doped infinite-layer NdNiO2 — a transition metal (TM) oxide that is both isostructural and isoelectronic to cuprate superconductors—has lead to renewed enthusiasm in the hope of understanding the origin of unconventional superconductivity. Here, we investigate the electron-removal states in infinite-layered Ni1+ oxide, NdNiO2, which mimics hole doping, with the state-of-the-art many-body multireference quantum chemistry methods. From the analysis of the many-body wavefunction we find that the hole-doped d8 ground state of NdNiO2 is very different from the d8 ground state in isostructural cuprate analog CaCuO2, although the parent d9 ground states are for the most part identical. We show that the doped hole in NdNiO2 mainly localizes on the Ni 3dx2−y2 orbital to form a closed-shell singlet, and this singlet configuration contributes to ∼40% of the wavefunction. In contrast, in CaCuO2 the Zhang-Rice singlet configurations contribute to ∼65% of the wavefunction. With the help of the quantum information concept of entanglement entropy, we quantify the different types of electronic correlations in the nickelate and cuprate compounds, and find that the dynamic radial-type correlations within the Ni d manifold are persistent in hole-doped NdNiO2. As a result, the d8 multiplet effects are stronger and the additional hole foot-print is more three-dimensional in NdNiO2. Our analysis shows that the most commonly used three-band Hubbard model employed to express the doped scenario in cuprates represents ∼90% of the d8 wavefunction for CaCuO2, but such a model grossly approximates the d8 wavefunction for NdNiO2 as it only stands for ∼60% of the wavefunction.